PR Media Relations Strategy In Improving The Quality Of Family Planning (Kb) Services In Ntt Province Population And National Family Planning Agency (Bkkbn) - Melva, Reki Dwi; Havifi, Ilham (Semantik: Journal of Social, Media, Communication, and Journalism, 2023)
The purpose of this study was to determine the Media Relations Public Relations Strategy of the National Population and Family Planning Board (BKKBN) of the NTT Province in Improving the Quality of Family Planning (KB) Services. The method used in this research is a type of qualitative research. It discusses in depth to better understand phenomena such as opinions, desires, feelings, and behavior of media relations regarding the strategies and media relations activities carried out by BKKBN. The scope of the research is in the Public Relations Section of the Office of the National Population and Family Planning Agency (BKKBN) of the Province of NTT which provides services to the community. Data collection techniques used in this study were interviews, observation and documentary studies. While the data analysis technique used is data analysis using descriptive qualitative analysis techniques. The results of the research conducted were the quality of service through the media relations strategy in the Public Relations of the BKKBN in the Province of NTT above. It can be concluded that the services through the strategy of media relations in the Public Relations of the BKKBN in the Province of NTT have gone well because: a) there is timeliness in providing information; b) provide information or news to the mass media in dealing with problems or issues that arise in society and the willingness to help customers and provide services quickly; c) generate trust and confidence, which is the ability of Public Relations in creating a sense of public trust in the NTT BKKBN including communication, credibility, security, competence and courtesy; d) provide information through the media or publications and conduct events for the community related to knowledge, specific community needs; and e) displaying physical facilities, equipment or technology and the appearance of employees at the NTT Coordinating and Family Planning Agency (BKKBN) Office